Impact of Tobacco Smoking on Outcomes After Posterior Decompression Surgery in Patients With Cervical Spondylotic Myelopathy: A Retrospective Multicenter Study. Issue 10 (December 2020) - Nagoshi, Narihito; Kono, Hitoshi; Tsuji, Osahiko; Aoyama, Ryoma; Fujiyoshi, Kanehiro; Shiono, Yuta; Ishikawa, Masayuki; Daimon, Kenshi; Hosogane, Naobumi; Takeuchi, Ayano; Okada, Eijiro; Fujita, Nobuyuki; et al.
Abstract : Study Design: This was a case-control study. Objective: The objective of this study was to clarify the surgical outcomes after cervical posterior decompression in patients who smoked. Summary of Background Data: Smoking is associated with poor outcomes in the field of spinal surgery. However, the impact of tobacco smoking on the outcomes after posterior decompression surgery has not been fully evaluated in patients with cervical spondylotic myelopathy. Materials and Methods: In this retrospective multicenter study, 587 patients with cervical spondylotic myelopathy were enrolled at 17 institutions in Japan. Patients underwent cervical laminoplasty or laminectomy and were followed up for at least 1 year after surgery. Outcome measures were: preoperative smoking status, perioperative complications, the Japanese Orthopedic Association scale, and the Visual Analog Scale for neck pain. After adjusting for age and sex by exact matching, smoking and nonsmoking groups were compared using an unpaired t test for continuous variables or a χ 2 test for categorical variables. Results: There were 182 (31%) current smokers and 405 (69%) nonsmokers including previous smokers. After matching, 158 patients were extracted from each group. Demographic data and surgical information were almost the same between the groups. Regarding postoperative complications, there was no significant difference in the rate of surgical site infection, cerebrospinal fluid leakage, hematoma, segmental motor paralysis, or neurological deficit. However, smokers showed a significantly higher risk for delirium (3.8% vs. 0.0%, P =0.039). Smokers and nonsmokers showed comparable changes in functional recovery according to Japanese Orthopedic Association scores (3.2±2.1 vs. 3.0±2.1, P =0.425) and in neck pain reduction using the Visual Analog Scale (−1.7±3.1 vs. −1.4±2.8, P =0.417) at the final follow-up. Conclusions: Smokers exhibited functional restoration and neck pain reduction after cervical posterior decompression. Attention is required, however, for the postoperative complication of delirium, which could be caused by the acute cessation of tobacco smoking after admission. Level of Evidence: Level III.